Marginal Information: shifts in news discourse through satire and provocation - Laport, Gracy (Revista do Colóquio, 2026)
Sob o editorial regime that imposes censorship and apagamento of individual sayings and sobre an artistic production and of information between our years of 1964 and 1985 no Brasil, insurgent movements that deslocam or lugar of the notícia and of acontecimento, agora não but circunspectos our meios tradicionais de informação ou na imprensa hegemônica. The movement does not take place in the context of Brazil experiencing the Covid-19 pandemic under the command of former President Jair Bolsonaro in an extreme regime. This art is intended to be analyzed by Quem Matou Herzog?, by the Brazilian artist Cildo Meireles, and by the project #QuarentenaProjetada as our margins of information that subvert the dominant order and use of publishing, circulation and intervention to release or implement it. social perception of reality.
Keywords: information; art; dictatorship; Covid-19 pandemic; marginal